Analisis Kemampuan Berpikir Reflektif Matematis Siswa Ditinjau dari Kegigihan dan Ketekunan dalam Pemecahan Masalah Teorema Pythagoras - Rizka Sri Windy Arini; Rita Destini; Cut Latifah Zahari (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
This study analyzes junior high school students' mathematical reflective thinking when viewed from the aspect of persistence and perseverance in solving mathematical problems. The focus was drawn from one research question concerning how students' reflective thinking appears in relation to their perseverance when working on Pythagorean theorem tasks. A qualitative case-study design was employed at SMP Negeri 1 Tanjung Morawa involving 29 students of class VIII-1, with 9 students selected purposively for deeper analysis based on variations in productive disposition. Data were collected through written reflective-thinking tests, a productive-disposition questionnaire, semi-structured interviews, observation, and documentation. The data were analyzed descriptively through reduction, coding, categorization, presentation, conclusion drawing, and triangulation. The findings show that students with strong persistence were more capable of identifying procedural and conceptual errors, revising inappropriate formulas, explaining the relationship among sides of a right triangle, and continuing the solution process until a more accurate answer was obtained. Students with moderate persistence began to recognize and correct errors but still needed guidance to justify their reasoning consistently. Students with weak persistence tended to stop at the first answer, relied on external help, and showed limited self-evaluation. The study concludes that persistence and perseverance support reflective mathematical thinking by sustaining students' efforts to review, evaluate, and improve their problem-solving processes